Health assessment of snacks and desserts in Guizhou Province: Analysis of fatty acids and sugar content - Lu Zou; Xianjie Fu; Junfei Huang; Wenzheng Liu; Liqiang Zhou; Yibing Zhou; Ye Lin; Liya Liu (PLoS ONE, 2025)
Introduction Dietary patterns, particularly the excessive consumption of snacks high in fats and sugars, remain a pivotal factor producing adverse impact on the global prevalence of obesity and chronic diseases. However, the current situation is that there is insufficient study on the nutritional value and health risks of local snacks and desserts of Guizhou Province. To fill this gap, this study aimed to analyze the fatty acid (FA) composition and sugar content of popular snacks and desserts in Guizhou Province. Methods A comprehensive nutritional evaluation was conducted on local snacks and desserts in Guizhou province, with a focus on the FA profile and five sugars (glucose, fructose, sucrose, maltose, and lactose). The study examined how cooking methods (steaming, baking, frying) and food classification (traditional vs. non-traditional) influence the nutritional profiles of these foods, which are predominantly made from rice, wheat, and cream. Results Rice-based foods, particularly those steamed using traditional methods, showed superior nutritional profiles. They had significantly lower crude fat (7.35±1.50 g/100g) and total FA (6.10±1.55 g/100g) compared to other methods. Trans fatty acid (TFA) content was minimal (0.0179±0.0137 g/100g), and atherogenic index (AI) and thrombogenic index (TI) were low at 0.19±0.07 and 0.38±0.27, respectively. Rice-based foods also had an acceptable sugar content with no lactose, suitable for lactose-intolerant individuals. Among the rice-based foods, Rice Tofu (RT) had the best performance with the lowest Crude Fat (5.98 g/100g), AI (0.04), TI (0.05), highest monounsaturated FA (MUFA) content (3.11 g/100g), polyunsaturated FA (PUFA) to saturated FA (SFA) ratio (8.48), and n-3PUFA/n-6PUFA ratio (0.25), along with acceptable sugar levels. Conclusion The nutritional value of snacks varies widely due to differences in raw materials, cooking methods, and traditional preparation techniques. Traditional steamed rice products, especially RT, offer the best nutritional profile and can be promoted as representative healthy traditional foods in Guizhou Province.